FROM TOTALITARIANISM TO DEMOCRACY IN BULGARIA (Revista Ciencias de la Documentación, 2020)
The transition from a totalitarian regime to a democratic political system in Bulgaria has its particularities. They are based on specifics as history, geographical location, international situation, political culture, economy etc. Liberal democracy nowadays has been criticized and challenged as governance for the unsuccess in certain spheres. Security has replaced freedom as a core value. Totalitarian political ideologies are not possible, but there exist other challenges to democracy in Bulgaria.